The ordinary things we do a research-based video installation on the construction of marriage among selected Filipino same-sex copules - Corpuz, David Redulfin 1986- (College of Mass Communication, University of the Philippines Diliman, 2014)
"This thesis gathers narratives of Filipino same-sex couples in committed relationship to unearth their construction of marriage, an inaccessible institution to them as it is exclusive to heterosexual partnerships. Through in-depth interviews and analysis of available documents about same-sex weddings in the Philippines and through the guidance of social construction theory, romantic love myth, and the concept of heteronormativity as interpretive lenses, the study revealed that same-sex couples rely on the social definitions of marriage in making sense of their relationships. Have a dream wedding, living under a conjugal home, and yearning for a monogamous, permanent union emerge as some of the prevalent aspirations of these couples, which are indicative of the power of marriage as an unchallenged and idealized structuring institution. Acknowledging the dearth of media discussions about same-sex marriage in the Philippines, it is in the contention of this study to translate the construction of marriage into film, in the form of a video installation. The film attempts to show the core of the relationship that marriage and the festivities and symbols of the wedding have overshadowed and concealed: the two individuals within it. Guided by the principles of counter-cinema, cubism, and video art, the video installation shows a visualization of the multiple perspectives of the research and addresses the deconstruction of heteronormative binaries that are evident in the discussion of marriage."